Development of Multiply Card as Multiplication Learning Media in Elementary Schools - Evi Faujiah; Herlina Usman; Achmad Khomsin; Vina Shelfiana (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to develop the Multiply Cards game as a medium for learning mathematics in additional material in elementary schools that is interesting, metacognitive, and connection-based. This type of research is research and development (R&D) according to the ADDIE development model which consists of five stages, namely: analysis, design, development, implementation, and evaluation. The subjects of this study were class students at SDN Mekarsari 5, Kec II.Cimanggis, Depok City. The research tools consisted of material expert validation instruments, media expert validation instruments, teacher validation instruments, and student and teacher response questionnaires. Based on the evaluation of the validity test, the validation results of the material experts were considered